Elizabethkingia meningoseptica infection in a geriatric patient with other recurrent bacterial infections - Luis Castañeda Pelaez; Jesús Eduardo Rojas Jaimes; Elsa Nuñez Infanzón; Delza Tárraga Gonzales; Sergio Ronceros Medrano (eNeurologicalSci, 2025)
Elizabethkingia meningoseptica is a Gram-negative bacillary bacterium known for its multidrug resistance, particularly to carbapenems. This resistance complicates treatment and results in a high mortality rate, especially in hospitalized patients, which can reach up to 52 %. In this case, the infection was observed in a 73-year-old immunocompetent patient with a chronic exacerbated subdural hemorrhage with midline deviation and tracheostomy, who was hospitalized and febrile, and the bacterium Elizabethkingia meningoseptica was isolated in bronchial secretion cultures. The patient responded favorably to treatment with sulfamethoxazole/trimethoprim and other recurrent infections caused by Klebsiella pneumoniae, Stenotrophomonas maltophilia, and Pseudomonas aeruginosa. Ultimately, the immunocompetent patient improved and was discharged, able to ventilate independently.